Alternative splicing modifies the effect of mutations in COL11A1 and results in recessive type 2 Stickler syndrome with profound hearing loss. Issue 11 (6th August 2013) - Richards, Allan J; Fincham, Gregory S; McNinch, Annie; Hill, David; Poulson, Arabella V; Castle, Bruce; Lees, Melissa M; Moore, Anthony T; Scott, John D; Snead, Martin P
Abstract : Background: Stickler syndromes types 1, 2 and 3 are usually dominant disorders caused by mutations in the genes COL2A1, COL11A1 and COL11A2 that encode the fibrillar collagens types II and XI present in cartilage and vitreous. Rare recessive forms of Stickler syndrome exist that are due to mutations in genes encoding type IX collagen ( COL9A1 type 4 Stickler syndrome and COL9A2 type 5 Stickler syndrome). Recently, recessive mutations in the COL11A1 gene have been demonstrated to result in fibrochondrogenesis, a much more severe skeletal dysplasia, which is often lethal. Here we demonstrate that some mutations in COL11A1 are recessive, modified by alternative splicing and result in type 2 Stickler syndrome rather than fibrochondrogenesis. Methods: Patients referred to the national Stickler syndrome diagnostic service for England, UK were assessed clinically and subsequently sequenced for mutations in COL11A1 . Additional in silico and functional studies to assess the effect of sequence variants on pre-mRNA processing and collagen structure were performed. Results: In three different families, heterozygous COL11A1 biallelic null, null/missense or silent/missense mutations, were found. They resulted in a recessive form of type 2 Stickler syndrome characterised by particularly profound hearing loss and are clinically distinct from the recessive types 4 and 5 variants of Stickler syndrome. One mutant allele in each family is capable of synthesising a normal α1(XI) procollagen molecule, via variable pre-mRNA processing. Conclusion: This new variant has important implications for molecular diagnosis and counselling families with type 2 Stickler syndrome.